2019
DOI: 10.1016/j.paid.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The bright side of dark: Exploring the positive effect of narcissism on perceived stress through mental toughness

Abstract: We gratefully acknowledge all the participants that took part in these three studies. We are particularly grateful to a number of undergraduate and MSc students that acted as research assistants and contributed to data collection at London Metropolitan University and Queen's University Belfast. The studies were not preregistered. Author Contributions K.A.P. has written the manuscript and he was responsible for data collection and data preparation; F.M.G., D.B., P.W. and G.B.M. were responsible for data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Whereas some found positive associations among all 4Cs and narcissism, psychopathy, and Machiavellianism (Sabouri et al, ), others reported a positive correlation between MT and narcissism, but negative correlations among MT, psychopathy, and Machiavellianism (Onley et al, ). Similar associations (in terms of size and direction) emerged in another study, which reported that confidence is the strongest (out of the 4Cs) correlate of narcissism; a mediation effect such that narcissism reduces psychopathy and Machiavellianism (Papageorgiou et al, ); symptoms of depression (Papageorgiou, Denovan, et al, ); and perceived stress (Papageorgiou, Gianniou, et al, ), through MT. This mediation model has also been tested using longitudinal data and showed that narcissism may increase MT resulting in higher school grades in an adolescent sample (Papageorgiou, Malanchini, et al, ).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Whereas some found positive associations among all 4Cs and narcissism, psychopathy, and Machiavellianism (Sabouri et al, ), others reported a positive correlation between MT and narcissism, but negative correlations among MT, psychopathy, and Machiavellianism (Onley et al, ). Similar associations (in terms of size and direction) emerged in another study, which reported that confidence is the strongest (out of the 4Cs) correlate of narcissism; a mediation effect such that narcissism reduces psychopathy and Machiavellianism (Papageorgiou et al, ); symptoms of depression (Papageorgiou, Denovan, et al, ); and perceived stress (Papageorgiou, Gianniou, et al, ), through MT. This mediation model has also been tested using longitudinal data and showed that narcissism may increase MT resulting in higher school grades in an adolescent sample (Papageorgiou, Malanchini, et al, ).…”
Section: Introductionsupporting
confidence: 57%
“…However, other researchers have argued that grouping DT traits together may not be particularly informative (e.g., Papageorgiou, Wong, & Clough, ). In particular, several studies examining the association among narcissism and other traits, performance measures, and psychopathology symptoms (e.g., Ng, Cheung, & Tam, ; Onley, Veselka, Schermer, & Vernon, ; Papageorgiou et al, ; Papageorgiou, Malanchini, et al, ; Papageorgiou, Denovan, & Dagnall, ; Papageorgiou, Gianniou, et al, ; Petrides, Vernon, Schermer, & Veselka, ; Sabouri et al, ; Sedikides, Rudich, Gregg, Kumashiro, & Rusbult, ; Veselka, Schermer, & Vernon, ; Zeigler‐Hill & Besser, ) suggested that the inclusion of narcissism in the malevolent side of human personality may need to be reconsidered.…”
Section: Introductionmentioning
confidence: 99%
“…We attempted to understand mean‐level differences and variance in sex differences as a function of a wide range of economic, political, and social factors around the world. We tested scarcity and liberalization hypotheses (Campbell & Żemojtel‐Piotrowska, 2017; Papageorgiou et al., 2019; Twenge & Campbell, 2010) in relation to country‐levels of the Dark Triad traits along with variance in the sex differences from country‐to‐country. The results were more consistent with the scarcity hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if personality traits are responses to local conditions, how should a trait like narcissism respond to different conditions? One hypothesis suggests that narcissism is created by a culture of indulgence or liberalization (Foster, Campbell, & Twenge, 2003; Miller et al., 2015; Twenge & Campbell, 2010), whereas an alternative view suggests that it might be created by scarcity (Campbell & Żemojtel‐Piotrowska, 2017; Papageorgiou et al., 2019). Regarding the latter view, in countries that are less developed, more corrupt, and have less economic freedom, peace, and gender equality, there is likely a greater degree of scarcity increasing competition for resources.…”
Section: Introductionmentioning
confidence: 99%
“…In a general context, MT serves as an umbrella term to denote enabling psychological resources across a range of achievement contexts that promote positive mental health (Lin et al, 2017; Drinkwater et al, 2019; Papageorgiou et al, 2019a, b). Such universality can give rise to terminology that lacks a sound empirical basis, is theoretically vague, and contributes to conceptual obfuscation.…”
Section: Introductionmentioning
confidence: 99%